Implementation of Outdoor Play (Cube Jumping and Glass Flipping) to Develop Early Childhood Rough Motorcycles at Muslimat NU 1 Pamekasan Kindergarten - Harisah; Dewi Pusparini; Musayyadah (STIT Attaqwa, 2024)
Outdoor activities are play equipment outside the classroom that can be used as a means of play that contains educational value and develops all aspects of early childhood development. This research aims to analyze the implementation of outdoor play activities to develop gross motor skills in early childhood at the Muslimat NU 1 Pamekasan Kindergarten. This research use desciptive qualitative approach. The subjects in this research were the principal and class A class B teacher at Muslimat NU 1 Kindergarten. Data collection used in this research was observation, interviews and documentation, data analysis was carried out by data condensation, data presentation and conclusions. The results of this research show that from observations at the Muslimat NU 1 Pamekasan Kindergarten, it can be seen that gross motor development through outdoor activities is very effective. Outdoor play activities not only develop gross motor skills but can develop all aspects of a child's development. This also influences the moral and religious development of children and can be stimulated.